Callas in Concert: on the hologram, memory and presence - Rojas Parma, Lorena (Revista de Filosofía, 2020)
The article proposes a critical reflection on the phenomenon of the hologram in concert, through the “Callas in Concert”, in the Rose Hall at Lincoln Center. To do this, the image, reproduction and imitation of the hologram, in relation to the original, and the quality of that aesthetic experience, are discussed. Also, the study analyses its pharmakon function for human memory, the deep differences it keeps with memory, and how it can affect our relationships with the past and, finally, if the “hologram in concert” is some kind of evidence, so to speak, of the “irreplaceable” condition –as Gadamer says– of the live experience.